Bromide supplementation exacerbated the renal dysfunction, injury and fibrosis in a mouse model of Alport syndrome. - Tsubasa Yokota; Kohei Omachi; Mary Ann Suico; Haruka Kojima; Misato Kamura; Keisuke Teramoto; Shota Kaseda; Jun Kuwazuru; Tsuyoshi Shuto; Hirofumi Kai (PLoS ONE)
A seminal study recently demonstrated that bromide (Br-) has a critical function in the assembly of type IV collagen in basement membrane (BM), and suggested that Br- supplementation has therapeutic potential for BM diseases. Because salts of bromide (KBr and NaBr) have been used as antiepileptic drugs for several decades, repositioning of Br- for BM diseases is probable. However, the effects of Br- on glomerular basement membrane (GBM) disease such as Alport syndrome (AS) and its impact on the kidney are still unknown. In this study, we administered daily for 16 weeks 75 mg/kg or 250 mg/kg (within clinical dosage) NaBr or NaCl (control) via drinking water to 6-week-old AS mice (mouse model of X-linked AS). Treatment with 75 mg/kg NaBr had no effect on AS progression. Surprisingly, compared with 250 mg/kg NaCl, 250 mg/kg NaBr exacerbated the progressive proteinuria and increased the serum creatinine and blood urea nitrogen in AS mice. Histological analysis revealed that glomerular injury, renal inflammation and fibrosis were exacerbated in mice treated with 250 mg/kg NaBr compared with NaCl. The expressions of renal injury markers (Lcn2, Lysozyme), matrix metalloproteinase (Mmp-12), pro-inflammatory cytokines (Il-6, Il-8, Tnf-α, Il-1β) and pro-fibrotic genes (Tgf-β, Col1a1, α-Sma) were also exacerbated by 250 mg/kg NaBr treatment. Notably, the exacerbating effects of Br- were not observed in wild-type mice. These findings suggest that Br- supplementation needs to be carefully evaluated for real positive health benefits and for the absence of adverse side effects especially in GBM diseases such as AS.